1998
DOI: 10.1046/j.1365-2958.1998.00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the proteolytic pathway for use of β‐casein by Lactococcus lactis

Abstract: SummaryAmino acid auxotrophous bacteria such as Lactococcus lactis use proteins as a source of amino acids. For this process, they possess a complex proteolytic system to degrade the protein(s) and to transport the degradation products into the cell. We have been able to dissect the various steps of the pathway by deleting one or more genes encoding key enzymes/components of the system and using mass spectrometry to analyse the complex peptide mixtures. This approach revealed in detail how L. lactis liberates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 20 publications
4
68
0
Order By: Relevance
“…For high-affinity interaction with DtpT, the peptides need to have free amino and carboxyl termini, amino acids in the L configuration, and trans-peptide bonds. Comparison of the specificity of DtpT with that of the eukaryotic homologues PepT 1 and PepT 2 shows that the bacterial transporter is more restrictive in its substrate recognition.Studies of the transport of peptides across the cell membrane of Lactococcus lactis have established that the organism uses at least three distinct peptide transport systems (5,17,20,21,32,35,36; Y. Sanz Herranz, F. C. Lanfermeijer, W. N. Konings, and B. Poolman, submitted for publication). In addition to the ATP-dependent ATP-binding cassette (ABC)-type of oligo-and di-and/or tripeptide transport systems, Opp and DtpP, respectively, L. lactis possesses a proton motive force-driven di-and/or tripeptide transporter DtpT.…”
mentioning
confidence: 99%
“…For high-affinity interaction with DtpT, the peptides need to have free amino and carboxyl termini, amino acids in the L configuration, and trans-peptide bonds. Comparison of the specificity of DtpT with that of the eukaryotic homologues PepT 1 and PepT 2 shows that the bacterial transporter is more restrictive in its substrate recognition.Studies of the transport of peptides across the cell membrane of Lactococcus lactis have established that the organism uses at least three distinct peptide transport systems (5,17,20,21,32,35,36; Y. Sanz Herranz, F. C. Lanfermeijer, W. N. Konings, and B. Poolman, submitted for publication). In addition to the ATP-dependent ATP-binding cassette (ABC)-type of oligo-and di-and/or tripeptide transport systems, Opp and DtpP, respectively, L. lactis possesses a proton motive force-driven di-and/or tripeptide transporter DtpT.…”
mentioning
confidence: 99%
“…In case of L. lactis it has been shown that β-casein is degraded to peptides of five to 30 amino acid residues, and a substantial fraction of these is imported into the cell via Opp. It has been shown that Opp of L. lactis accepts peptides in the range of five to ten residues when it is supplied with a complex mixture of β-casein-derived peptides [28]. This surprising finding was corroborated later on in studies with individual peptides of various lengths, where it was shown that peptides up to at least 18 residues are transported [10].…”
Section: Source Of Nitrogen and Metabolic Energymentioning
confidence: 87%
“…During six growth curve replicates, the strain which lacked both the wild-type chromosomal and plasmid copy of aspC never acidified milk to more than 0n20 pH units below that of the blank and did not grow at a detectable rate. As oligopeptides liberated from caseins by the lactococcal PrtP serve as the major nitrogen source for L. lactis in milk (Juillard et al, 1995a), and L. lactis can apparently transport and hydrolyse at least one Asp-containing peptide from β-casein (Kunji et al, 1998), the inability of JLS400(pJK550, pTRKL2) to rapidly grow in or acidify milk suggests L. lactis is unable to liberate an adequate level of Asp or Asn from milk caseins to support optimal growth. As Asp is the biosynthetic precursor for Asn, threonine, lysine and methionine, as well as pyrimidine and purine nucleotides, Asp biosynthesis may also be essential for supplying the cell with sufficient levels of these biological compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro data suggests that lactococci can obtain all amino acids through hydrolysis and transport of β-casein-derived oligopeptides (Juillard et al, 1995b). However, more recent in vivo studies have shown that lactococci utilize only a limited number of oligopeptides derived from the C-terminal end of β-casein (Kunji et al, 1998).…”
Section: -4342 # 2001 Sgmmentioning
confidence: 99%